Asymmetric‐Indenothiophene‐Based Copolymers for Bulk Heterojunction Solar Cells with 9.14% Efficiency. Issue 17 (1st March 2016) - Wang, Meng; Cai, Dongdong; Yin, Zhigang; Chen, Shan‐Ci; Du, Cheng‐Feng; Zheng, Qingdong
Abstract : The first two asymmetric‐indenothiophene‐based donor–acceptor copolymers (PITBT and PITFBT) are prepared through Stille coupling reactions between distannyl indenothiophene and brominated benzothiadiazole derivatives. The best performing solar cell fabricated from PITFBT exhibits a power conversion efficiency of 9.14% which demonstrates a great potential of the asymmetric indenothiophene for high‐performance copolymers.